PERTANGGUNGJAWABAN PIDANA TERHADAP PIHAK MANAJEMEN SELEBRITAS ATAS ENDORSEMENT PRODUK JUDI ONLINE - Farizy Gusniarto, (2023)
This study aims to determine the elements of inclusion or criminal assistance in accepting endorsements by celebrity management and to analyze criminal liability for celebrity management who receive online gambling endorsements. This type of research is normative legal research. Approach The problem used is a statutory approach and a conceptual approach. Sources of data are obtained from primary legal materials originating from statutory regulations; secondary materials originating from legal sources other than laws; and tertiary legal materials that come from further secondary sources. The method of collecting data is literature study with technical data analysis in the form of descriptive and prescriptive analysis and qualitative methods. The results of the study explain that online gambling endorsement cases carried out by celebrities actually involve management. This is an inclusion of criminal acts that often escape the law. In the case of online gambling endorsements, celebrity management is classified as an advocate/movers (uitlokker) or can also be known as an intellectualist actor and celebrities who advertise online gambling products are executors (pleger) and have a position as materialist actors. As well as the celebrity management so that they can be held criminally responsible in online gambling endorsement cases, it is necessary to fulfill the conditions including, then management's intention to encourage the celebrity to commit a crime, the emergence of the psychological will of the celebrity, the recommended celebrity embodying the act or at least trials, and the recommended celebrities are those capable of criminal responsibility.